2022
DOI: 10.1080/21645515.2022.2100189
|View full text |Cite
|
Sign up to set email alerts
|

A personal COVID-19 dendritic cell vaccine made at point-of-care: Feasibility, safety, and antigen-specific cellular immune responses

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a world-wide pandemic. Internationally, because of availability, accessibility, and distribution issues, there is a need for additional vaccines. This study aimed to: establish the feasibility of personal dendritic cell vaccines to the SARS-CoV-2 spike protein, establish the safety of a single subcutaneous vaccine injection, and determine the antigen-specific immune response following vaccination. In Phase 1, 31 subjects were assigned to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…However, there is growing evidence that the T-cell response plays a significant role in the elimination of the COVID-19 virus and is thought to play a central role in forming broad-spectrum and long-term immunity ( 24 26 ). In this clinical trial, monitoring for up to 28 days showed that vaccine administration could trigger an optimal specific T-cell response to SARS-CoV-2 ( 8 ). Data from phase I also show good induction of humoral responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is growing evidence that the T-cell response plays a significant role in the elimination of the COVID-19 virus and is thought to play a central role in forming broad-spectrum and long-term immunity ( 24 26 ). In this clinical trial, monitoring for up to 28 days showed that vaccine administration could trigger an optimal specific T-cell response to SARS-CoV-2 ( 8 ). Data from phase I also show good induction of humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…AEs that occur up to 28 days post-vaccination, based on reported data, are all mild. Non-COVID AE for up to 28 days was reported by 64.5% of phase I subjects and 53.6% of phase II subjects, and there were no significant differences between treatment groups ( 8 ). Similarly, in follow-ups from 1 to 12 months, the total incidence of non-COVID AE in phase I was 35.71% of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study has shown that ex vivo DC incubation with peptides from the S-protein SARS-CoV-2 can elicit an immunogenic response in the body through the response of T cells and B cells. 15,16 However, this case suggests the possibility that the DC vaccine can also control autoimmune through the tolerogenic response of the DC. Several things that need to be considered in future research are the possibility of special conditions or factors that can cause a tolerogenic response from DC introduced to the SARS-CoV-2 S-protein, such as autoimmune conditions triggered after SARS-CoV-2 infection, genetic variations of DC obtained from people with autoimmune diseases, or the use of immunosuppressive agents such as vitamin D3 and glucocorticoid.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 98%